Effectiveness of positive and negative ions for elite Japanese swimmers` physical training: Subjective and biological emotional evaluations - Hagiwara, G.; Mankyu, H.; Tsunokawa, T.; Matsumoto, M.; Funamori, H. (Applied Sciences, 2020)
The purpose of this study is to examine the subjective and objective arousal of elite swimmers during physical training under a positive and negative ion environment. The participants were 10 elite Japanese collegiate swimmers participating in the Fédération Internationale de Natation (FINA) Swimming World Cup (age: 20.80 ± 1.39, five males and five females). Each participant went through two experiments (they were subjected to both the positive and negative ion environment and the control environment) within a four-week interval. The training task was a High-Intensity Interval Training (HIIT) routine for the swimmers. The subjective arousal state was measured using a Two-Dimensional Mood Scale (TDMS). In addition, biological emotional evaluations in the form of an electroencephalogram (EEG) were conducted to assess the arousal state of the elite swimmers. The examination of the change in the arousal level at rest and during training demonstrated that both subjective and objective arousal levels were significantly higher in the positive and negative ion environment than in the control environment. In addition, the average training performance scores were also significantly higher in the positive and negative ion environment than in the control environment. This study posits that the positive and negative ion environment has a positive effect on sports training.